2016
DOI: 10.1371/journal.pone.0165734
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Research Bronchoscopy in Malawian Adults with Pulmonary Tuberculosis: A Cross-Sectional Study

Abstract: Bronchoscopy is an established research tool in Malawi, enabling collection of pulmonary samples for immunological, pharmacological, and microbiological studies. It is, however, an invasive clinical procedure that offers no direct benefit to volunteering participants when used in a research capacity alone, and thus informed consent is essential. This study aimed to explore TB patients’ understanding of research bronchoscopy, what would motivate them to participate in research bronchoscopy, and their concerns, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Appropriate payment was related to the basic minimum wage ($3.50 per day) and to the amount a person might earn in the market selling goods ($80-300) 16 . In a study of prospective participants in research bronchoscopy in Malawi, focus group discussion confirmed that remuneration for travel, food and lost earnings would be sufficient 33 and follow-up with these authors confirms that focus group discussion participants did in fact attend for multiple bronchoscopies…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Appropriate payment was related to the basic minimum wage ($3.50 per day) and to the amount a person might earn in the market selling goods ($80-300) 16 . In a study of prospective participants in research bronchoscopy in Malawi, focus group discussion confirmed that remuneration for travel, food and lost earnings would be sufficient 33 and follow-up with these authors confirms that focus group discussion participants did in fact attend for multiple bronchoscopies…”
Section: Resultsmentioning
confidence: 84%
“…There is a long tradition of both community- and hospital-based research in Malawi, and remuneration has been used in each of the three categories discussed above. As in other regions, financial remuneration is not the key motivational factor underpinning research participants involvement decisions in Malawi 14 and Kenya 23 — participant considerations of gaining access to otherwise inaccessible health care, examination and medical tests are equally if not more important 33 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The use of bronchoscopy as a research tool has mainly been limited to patients with clinical lung disease [1]. However, recent studies of healthy individuals exposed to patients with TB have begun to examine human protective immune responses against TB [2,3]. Little is known about the reasons that motivate otherwise healthy individuals to undergo or decline research bronchoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous exploration of reasons for participation in research bronchoscopy studies among volunteers in Africa [2]. Europe and the United States revealed personal benefit, including health assessment, perceived future access to health care when ill, and remuneration as factors influencing willingness to undergo bronchoscopy.…”
Section: Introductionmentioning
confidence: 99%